Evaluation and usage scenarios of open source digital library and collection management tools. Issue 3 (6th July 2015) - Gkoumas, Georgios; Lazarinis, Fotis
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to evaluate open source software (OSS) for digital libraries and collection management and to propose different utilization scenarios based on the characteristics of the tools. Design/methodology/approach – The tools are assessed on the basis of their technical features and options, the type of the content they manage, the support for common library operations such as cataloging and circulation, the searching support and the interoperability options. Then they are evaluated by users and finally a number of usage scenarios are analyzed based on the results of the evaluation. Findings – The basic findings of the study is that open source digital library and collection management tools offer advanced operations and support various metadata and interoperability protocols with easy and user-friendly interfaces. Most of the tools are extensively used under various settings and establishments already. Language support for the interfaces should be extended with more languages and some tools with limited operations should be improved to be of practical use. Practical implications – The findings of the paper could be used support the selection of specific open source tools for various types of establishments. Originality/value – The study reviews the characteristics of a few OSS for digital libraries and collection management and reveals their specific strengths and weaknesses. It also presents a number of realistic scenarios and proposes the usage of specific tools based on time, technology and staff constraints.